APPLICATION OF SOCIAL GROUP ACTIVITY THERAPY IN SCIZOPHRENIAN PATIENTS WITH SOCIAL ISOLATION IN THE HOSPITAL OF JIWA PROF DR SOEROJO MAGELANG - emilia puspitasari sugiyanto (Jurnal Manajemen Asuhan Keperawatan, 2021)
Social isolation is the client's effort to avoid interaction with others. Therapy is given to patients with social isolation by providing social group activity therapy. Social group activity therapy is a group activity therapy with learning activities stages of communication with others to improve the ability to socially relate. The purpose of social group activity therapy is to facilitate the ability of patients with social relationship problems so as to improve the ability and train patients in socializing to minimize the number of patients with mental disorders. The purpose of this case study is to compose a resume of nursing care in the application of social group activity therapy to train patients in reducing the symptoms of social isolation. This type of research is descriptive with a case study method. The subjects of this study were patients with schizophrenia, patients withdrawing, patients who had already gotten the strategy of implementing 2 social isolation. The results of the study showed that there was a change in the decrease in social isolation signs before treatment of social group activity in Patient I by 27 symptoms and in Patient II in 24 symptoms after social group activity therapy in Patient I was 5 symptoms and Patient II was 5 symptom signs after giving social group activity therapy for 7 sessions so that patients are expected to be able to maintain socialization with others